1994
DOI: 10.1007/bf02087698
|View full text |Cite
|
Sign up to set email alerts
|

Loperamide improves anal sphincter function and continence after restorative proctocolectomy

Abstract: The physiological and clinical effects of loperamide treatment versus placebo were investigated in a randomized, double-blind, crossover study in patients operated with restorative proctocolectomy. Sixteen patients operated with endoanal mucosectomy and a handsewn ileal pouch-anal anastomosis and 14 patients operated with abdominal proctocolectomy and stapling of the pouch to the top of the anal canal were studied. While loperamide treatment increased resting anal pressure in both groups of patients by approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 23 publications
0
39
0
4
Order By: Relevance
“…A placebocontrolled study of loperamide 4 mg tid has been shown to reduce the frequency of incontinence, improve stool urgency and increase colonic transit time (84), as well as increase anal resting sphincter pressure (137) and reduce stool weight (138). Clinical improvement was also reported with diphenoxylate/atropine (Lomotil ® ) (139) but, objective testing showed no improvement in their ability to retain saline or spheres.…”
Section: Specific Treatmentmentioning
confidence: 99%
“…A placebocontrolled study of loperamide 4 mg tid has been shown to reduce the frequency of incontinence, improve stool urgency and increase colonic transit time (84), as well as increase anal resting sphincter pressure (137) and reduce stool weight (138). Clinical improvement was also reported with diphenoxylate/atropine (Lomotil ® ) (139) but, objective testing showed no improvement in their ability to retain saline or spheres.…”
Section: Specific Treatmentmentioning
confidence: 99%
“…Results demonstrated that the administration of antidiarrheal agents resulted in more patients achieving full continence compared with placebo. 29,31,32 Decreased episodes of fecal incontinence, fecal urgency, and occurrence of unformed stools have been noted as well. 26,27 With an overall decrease in incontinent symptoms, patients treated with constipating agents also were noted to have decreased fecal weight and water contents.…”
Section: C: Constipating Agentsmentioning
confidence: 91%
“…Loperamide inhibits small and large intestinal peristalsis, increases oralcecal transit time, and increases the mucosal exposure to intestinal effluent. 29,33 In addition, loperamide has been shown to improve anorectal physiology in normal volunteers and patients with diarrhea and to decrease stool frequency. Loperamide increases resting anal sphincter tone, improves rectal perception, increases the threshold of the rectoanal inhibitory reflex (RAIR), and increases fluid load retention in the rectum.…”
Section: C: Constipating Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…O uso de agentes formadores de massa, anticolinérgicos, opióides, antidepressivos, e outras drogas, são eficazes apenas na minoria dos casos de incontinência leve, ou como medidas adicionais a outros tipos de tratamento 41,42 . Outras medidas terapêuticas que surtem algum efeito para casos menos graves são o uso plugs e o biofeedback, sendo este último muito aplicado também como medida complementar ao tratamento cirúrgico [43][44][45] .…”
Section: Tratamentounclassified